Immunological evaluation of the crevicular fluid in patients with gingivitis, periodontitis, and peri-implantitis: a 1-year cross-sectional study (Research, Society and Development, 2021)
Objective:  To assess the levels of IL-12, IL-15, IL-18, and IL-32 in the gingival crevicular fluid (GCF) and peri-implant crevicular fluid (PICF) in patients with gingivitis, periodontitis, and peri-implantitis before and one year after implant installation. Material and Methods: Forty-nine samples of GCF and PICF were collected from March 2018 to March 2019. The patients were classified: patients with gingivitis (n=7), patients with periodontitis (n=14), patients with peri-implantitis (n=4) and healthy patients (n=24). The crevicular fluid from the 49 patients was collected before implant installation (n=8) and one year after implant placement (n=8). The Enzyme-Linked Immunosorbent Assay (ELISA) was used to evaluate the levels of cytokines in crevicular fluid. Results: Patients with gingivitis, periodontitis, and peri-implantitis showed higher concentrations of IL-12, IL-15, IL-18, and IL-32 when compared with control group. In general, the levels of IL-12 and IL-15 increased when compared to the moments before and after implant installation. There was also an increase in the concentration of IL-18 in the control group volunteers after implant installation. Conclusion: The results and methodology of this study showed that there was no difference in the synthesis of IL-12, IL-15, IL-18, and IL-32 in healthy individuals or in those with periodontal injuries. However, there was an increase in the cytokines IL-12, IL-15, and IL-18 one year after implant installation, which would be increasing the inflammatory activity in peri-implantitis.